Demographic changes and challenges in Europe with special focus on Germany - Moraal, Dick [Verfasser]; Schönfeld, Gudrun [Verfasser] (My University, 2011)
"The theoretical background of this chapter focuses at first on the analytical concept of transitional labour markets and then on transitions from the labour market into retirement/temporary disability and vice versa as well as from (long-term) unemployment of older persons to paid work and vice versa. These transitions, however, are not mere supply and demand processes, as the .push, pull, jump, stay, (re)entry' approach stipulates. Especially in Germany ageing of the population as well the labour force has had noticeable impacts since the beginning of 2010. Composition of the potential work force by age cohort will also change radically. German enterprises are particularly reliant on older employees and on retention of their employability and will be required to react to demographic pressure exerted by the predicted shortage of skilled employees and highly qualified staff. This chapter reports on the empirical findings of the third European continuing vocational training survey (CVTS3) and the German additional CVTS3 survey. Further, the findings of a Leonardo-II project examining continuing vocational training for older employees in SMEs are presented." (Autorenreferat, BIBB-Doku)
Keywords: P 1.8 Ältere; T 3.4 Befragung; I 2.1 Deutschland; I 2.2 Europa; Älterer Mensch; Älterer Arbeitnehmer; Beschäftigungsfähigkeit; Demografischer Wandel; Befragung; CVTS; Bundesrepublik Deutschland; Europa